Liber de Сausis. Capitula VII-XV - author, unknown (Sententiae, 2017)
The text was translated from Latin by Rostislav Paranko from Pattin, A. (Ed.). (1966). Le Liber de causis. Édition établie a l’aide de 90 manuscripts avec introduction et notes. Tijdschrift voor Filosofie, 28, 90-203. The translation is published with the permission of the UCU Publishing House, which plans to publish in the near future a full Ukrainian translation of "Liber de causis" with the comments of Andrei Baumeister.